User Study for In-Vehicle Displays - Le, Eva; Shi, Xiaoyan (My University, 2025)
This master’s thesis investigates how Head-Up Displays (HUDs) influence driver behaviour in real-world traffic, with a focus on attention, distraction, and cognitive load. The study examines a conventional HUD installed in a Volvo XC60 using eyetracking technology. A mixed-methods approach was employed, combining quantitative analysis of gaze dwell time and NASA-TLX scores with qualitative insights from thematic analysis of participant feedback. The research compares driver behaviours in HUD and non-HUD conditions. Findings indicate that while the presence of a HUD reduces visual attention to Head-Down Displays (HDDs) and is generally perceived as enhancing safety, usability concerns were raised—especially regarding the navigation interface. Although the HUD did not significantly affect the overall cognitive load, some participants reported visual discomfort. The study highlights both the potential benefits and challenges of HUD implementation and calls for further research with more diverse participants and multimodal HUD designs to ensure safe and user-friendly automotive interfaces.
Keywords: Head-Up Display; Eye-Tracking; Human-Computer Interaction; Interaction Design; User Experience; Usability; Automotive; Driver Behaviour; Attention; Distraction; Cognitive Load; Safety